2020
DOI: 10.1186/s13047-020-00433-9
|View full text |Cite
|
Sign up to set email alerts
|

Amputation rate of diabetic foot ulcer and associated factors in diabetes mellitus patients admitted to Nekemte referral hospital, western Ethiopia: prospective observational study

Abstract: Background Diabetes foot ulcer is a devastating and much-feared complication of diabetes. Diabetes foot ulcerations which developed gangrene can take weeks or months to heal and can sometimes not heal at all so that amputation for non-traumatic causes is a frequent outcome in the diabetic foot. Despite this, there is no finding on predictors of the amputation rate of diabetes foot ulcers in Ethiopia. Hence this study was aimed to identify factors associated with the amputation rate of diabetes foot ulcer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
0
31
1
2
Order By: Relevance
“…To improve the quality of life of diabetic patients, development of the effective treatments for diabetic complications has been necessary and urgent. Diabetic ulcers, the most common diabetic complication, a devastating medical problem which may lead to amputation (Alexiadou & Doupis, 2012; Bekele & Chelkeba, 2020; Guo et al, 2019). Traditional treatments include the control of blood glucose levels and healing management, but the therapeutic effect remains limited (Everett & Mathioudakis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the quality of life of diabetic patients, development of the effective treatments for diabetic complications has been necessary and urgent. Diabetic ulcers, the most common diabetic complication, a devastating medical problem which may lead to amputation (Alexiadou & Doupis, 2012; Bekele & Chelkeba, 2020; Guo et al, 2019). Traditional treatments include the control of blood glucose levels and healing management, but the therapeutic effect remains limited (Everett & Mathioudakis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that by 2030, the prevalence will increase to 10.2% and, by 2045, to 10.9% [ 1 ]. Among the most important complications of diabetes, the diabetic foot ulcer (DFU) emerges as a growing problem for public health systems since it is a leading cause of hospitalization and amputation in patients with diabetes [ 2 ]. Globally, the prevalence of DFU is estimated at 6.3%, and the highest prevalence has been found in North America (13.0%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infection and greater severity of DFU are associated with increased risk of amputation and mortality (Brennan et al, 2017 ; Ndosi et al, 2018 ). Studies have reported the rate of lower extremity amputation as high as 30.43% among DM patients with DFU in Ethiopia (Bekele et al, 2020 ; Bekele & Chelkeba, 2020 ). Both DFU and its ensuing infections increase the risk of emergency department visits and hospital admissions (Skrepnek et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%